General Properties of Beta-Galactosidase of Xanthomonas campestris - Frank, Joseph F. (1979)
Partially purified β-galactosidase of Xanthomonas campestris required 32 to 37°C and pH 5.5 to 5.8 for optimum activity. The enzyme had low affinity for lactose hydrolysis (K(m) = 22 mM) and was inhibited by thiol group reagents, ethylenediaminetetraacetic acid, galactose, and d-galactal.